2010
DOI: 10.1159/000319164
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Is Involved in the Response of the Isolated Intact and Epithelium-Denuded Rat Trachea to the β<sub>2</sub> Adrenergic Receptor Agonist Salbutamol

Abstract: Background: The involvement of the airway smooth muscle mediator nitric oxide (NO) in the actions of the β2 agonist salbutamol (Sal), a well- known bronchodilator, is very poorly understood. Objectives: To determine if endogenous NO release is a major factor in the Sal-induced relaxation of the carbachol- and electrical field-stimulated rat trachea and determine the role of the tracheal epithelium as the possible source of NO involved in these effects. Methods: Isolated carbachol- or electric field-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Recently, it was shown that salbutamol-induced relaxation in rat tracheas involves the relaxing action of NO [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that salbutamol-induced relaxation in rat tracheas involves the relaxing action of NO [30]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ENO may also be influenced by nondisease factors such as nitrate-containing foods [14], caffeine [15], alcohol [16], cigarette smoking [17], recent exercise [18], and some medications [19,20]. Due to these factors, ENO research protocols often incorporate more conventional measures of lung function, such as spirometric maneuvers (SPM), before and after bronchodilator administrations.…”
Section: Introductionmentioning
confidence: 99%